The educational role of the Accountants Association in Poland (AAP) after the deregulating of the profession - Świetla, Katarzyna (Rola edukacyjna Stowarzyszenia Księgowych w Polsce po deregulacji zawodu księgowego, 2018)
Due to the commonly perceived need to specialize in one professional activity, the role ofeducation is increasing. This includes accounting specializations which are important as professions ofpublic trust. In connection with such expectations, the role of education among professional groups ofaccounting professionals at all levels is increasing. The article presents the educational requirements forthe professional specialization on accounting against the IFAC International Education Standards and inthe context of the deregulation of the accountancy professions in Poland. As a solution to the problemsof appropriate education, the role of the Accountants Association in Poland (AAP) was pointed out,based on the courses provided by it, aimed at not only improving the qualifications of the individualswho are involved in accounting professionally, but also on the supporting ethics. The courses taughtwere analyzed in a cross-section of their participants in the years 2013-2016. The method adopted toachieve the intended purpose was the analysis of the available literature, the laws in force and the sourcesprovided by the AAP. On the basis of the research, it was found that despite the absence of mandatoryprofessional certification for accounting and bookkeeping, the professionals in this area do see the needfor continuous education and take diverse action to raise the quality of the services they provide
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 2, s. 75-89
Keywords: accounting; continuous training; education; certification; professional training; rachunkowość; nieustanne kształcenie; edukacja; certyfikacja; kursy zawodowe